Analysis of Young Entrepreneurs Behavior in Bima City from the Perspective of Islamic Business Ethics - Komariah, Nur; Syamsuddin, Ichwan P.; Al-Fajar, Muhammad Rasyad (STIT Sunan Giri Bima, 2025)
This study aims to examine the behavior of young entrepreneurs in the city of Bima from the perspective of Islamic business ethics. The business actors referred to in this study are members of independent business groups located in Bima City, specifically in the areas of Amahami Park, Mangge Maci Field, Serasuba Field, and Pahlawan Field. This research employs a qualitative approach with a case study strategy. Data collection techniques include observation, interviews, and direct documentation of the relevant subjects. Data validity is ensured through triangulation. The findings reveal five principles of Islamic business ethics practiced by young entrepreneurs. The first is the principle of tawhid or unity, which emphasizes the obligation to perform prayers when the time comes, upholding honesty, and avoiding riba (usury). Second, ensuring the protection of employee and consumer rights. Third, upholding the principle of free will by granting employees and consumers full freedom to use facilities, give suggestions, and choose products. Fourth, practicing the principle of responsibility by ensuring quality services, good product quality, and timely payment of salaries. Fifth, applying the principle of benevolence, as reflected in friendly and non-discriminatory customer service. In conclusion, from an Islamic perspective, young entrepreneurs in Bima City have implemented the principles of Islamic business ethics.